LANDASAN PENDIDIKAN ISLAM (Dalam Perspektif Tanggung Jawab Orang Tua, Masyarakat dan Negara) - Mizani, Hilmi; Mof, Yahya; Riyadh Maulidi, Ahmad (Al-Manba, 2023)
This study aims to reveal Islamic concepts about the foundation of Islamic education in terms of the responsibilities of parents, society and the state. The research method used is library research. The data to be extracted comes from the verses of the Qur'an, hadith texts, books, journals and magazines that contain Islamic concepts about the foundations of Islamic education in terms of the responsibilities of parents, society and the state. Analysis is used to analyze the data. content. This research resulted in findings that parents as institutions are first and foremost responsible for instilling religious values and social values so that children can carry out their functions as servants of God in the world. The community is responsible for participating in educating children so that the community is responsible for providing educational facilities in the form of physical facilities, as well as the values that apply in society. Meanwhile, the role of the state is to make various regulations to be used as a reference for the implementation of Islamic educational institutions. In addition, the role of the state is as a facilitator, as a companion, as a partner, and as a funder and supervisor of Islamic educational institutions.